2013
DOI: 10.1007/s12161-013-9672-y
|View full text |Cite
|
Sign up to set email alerts
|

Canine-Specific PCR Assay Targeting Cytochrome b Gene for the Detection of Dog Meat Adulteration in Commercial Frankfurters

Abstract: This report described a cytochrome b (cytb)-based polymerase chain reaction (PCR) assay for the detection of canine tissues in commercial frankfurters. Discriminating detection of canine derivatives in processed food products has important application in halal authentication as well as in health, religions, and fare trades. The assay based on a pair of canine-specific primers that targeted a 100 bp region of canine mithochondrial-cytb gene which is present in multiple copies and highly conserved within the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Canine Species Specificity Species-specific PCR assay is a commonly used technique for species authentication in raw and processed foods (Ali et al 2013;Mane et al 2009;Rahman et al 2014). The presence of a single mismatch in the primer binding site may reduce the efficiency of PCR assay or may lead to PCR amplification failure (Wu et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Canine Species Specificity Species-specific PCR assay is a commonly used technique for species authentication in raw and processed foods (Ali et al 2013;Mane et al 2009;Rahman et al 2014). The presence of a single mismatch in the primer binding site may reduce the efficiency of PCR assay or may lead to PCR amplification failure (Wu et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In c, Analysis of the primer mismatch and pairwise distance using 3D plot commercial food processing conditions, causing failure or truncated PCR products. We used here shorter DNA target (100 bp) and found that it was stable under various food processing treatments (Ali et al 2013;Rahman et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahman et al [5] have used PCR assay using cytochrome b gene as a target for detecting DM adulteration in meatball formulation. PCR assay using specific-specific primer on cytochrome b was also used for authentication of commercial Frankfurters from DM [12]. PCR using specific primer and restriction fragment length polymorphism (RFLP) was used for identification of meat sourced from cat, dog, donkey and horse [13].…”
Section: Introductionmentioning
confidence: 99%